PENGARUH PERKEMBANGAN TEKNOLOGI INFORMASI TERHADAP KEABSAHAN PERJANJIAN DALAM PERDAGANGAN SECARA ELEKTRONIK (E-COMMERCE) DI ERA GLOBALISASI - Lathifah Hanim (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Economic activity in the entire world with the existence of existence is increasingly dependent telematic technology. The development of Information technology giving influence on the validity of contracts in electronic commerce (E-Commerce) in the era of globalization and the what’s factors constraints on the validity of contracts in electronic commerce (E-Commerce) in the era of globalization. Article 1320 Civil Code is the principal instrument to test the validity of contracts made by the parties. Article 1320 Civil Code there are four legal conditions of contract, namely: agreements, the ability to create engagement, a certain thing, and a lawful reason. Contracts that do not meet the agreement and skill, resulting in the contract to cancel and void by law, if there are contracts that do not qualify or do not have a specific object or cause is not allowed, the resulting contract is null and void. Keywords: E-commerce, validity of agreement